Symptoms and esophageal motility based on phenotypic findings of scleroderma. Issue 2 (16th May 2012) - Tang, D. M.; Pathikonda, M.; Harrison, M.; Fisher, R. S.; Friedenberg, F. K.; Parkman, H. P.
SUMMARY: Scleroderma esophagus is characterized by ineffective peristalsis and reduced esophageal sphincter pressure. Esophageal disease in scleroderma can precede cutaneous manifestations and has been associated with Raynaud's phenomenon (RP) and pulmonary fibrosis (PF). The objective of the study is to evaluate the impact of cutaneous findings, RP, and PF on demographics, symptoms, and esophageal motility in patients with scleroderma. Scleroderma patients with esophageal involvement were included after review of esophageal manometries and charts over a 6‐year period. High‐resolution esophageal manometry was performed. Patients completed a symptom questionnaire. The study enrolled 28 patients (22 females; mean age 50.3 ± 12.8 years) with scleroderma esophagus. Patients without skin involvement ( n = 12) reported more severe heartburn ( P = 0.02), while those with cutaneous findings ( n = 16) had more frequent dysphagia with solids ( P = 0.02). Patients with RP ( n = 22) had lower amplitude of distal esophageal contractions ( P = 0.01) than those without RP ( n = 6). Patients with PF ( n = 11) reported more severe coughing and wheezing (both P = 0.03) than those without lung disease ( n = 17). This study highlights subgroups of patients with scleroderma esophagus according to phenotypic findings of dermatologic changes, RP, and PF. Heartburn and dysphagia are important symptoms that may be associated with different stages of disease progression based on skin changes in scleroderma. RP was associated with greater esophageal dysmotility. Coughing and wheezing were more severe in patients with PF.